Long-term prospective assessment of quality of life and physical function in malignant lymphoma patients undergoing chemotherapy - Ryuichi Kasahara; Takaaki Fujita; Ryohei Jinbo; Yuichi Yamamoto; Tatsuyuki Kai; Miki Furukawa; Hideo Kimura; Yasuyuki Taki; Jack B. Fu; Shinichiro Morishita (Medicine, 2026)
This study aims to evaluate longitudinal changes in health state utility values, health-related quality of life, physical function, nutritional status, and fatigue in patients with malignant lymphoma from the start of chemotherapy to 1 year post-chemotherapy and clarify the implications for survivorship care planning. This prospective observational study included 21 patients hospitalized for chemotherapy who also received exercise therapy. Assessments were conducted at baseline at admission, post-chemotherapy at discharge, as well as 6 months and 12 months after discharge (6M and 12M, respectively). Quality of life was assessed using the Short-Form 6-Dimension (SF-6D) and Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36); physical function using handgrip strength, knee extension strength, and the 6-minute walk test; nutritional status using the Mini Nutrition Assessment ® ; and fatigue using the Brief Fatigue Inventory. Temporal changes were analyzed using repeated measures analysis of variance with Bonferroni correction. SF-6D scores improved significantly from 0.571 ± 0.082 at baseline at admission to 0.693 ± 0.096 at 12M ( P < .01). Significant improvements were also found in most SF-36 domains over time, including physical functioning, role physical, general health, vitality, social functioning, role emotional, and mental health. Although no significant changes were observed in physical function, it remained stable throughout the study period. Mini Nutrition Assessment ® scores significantly improved at 6M ( P < .05), and Brief Fatigue Inventory scores significantly improved at both 6M and 12M ( P < .05 and P < .01, respectively). Chemotherapy patients with malignant lymphoma showed significant improvements in SF-6D, SF-36, and fatigue over the 1 year period following discharge, while physical function and nutritional status remained stable. These findings emphasize the need for ongoing rehabilitation and nutritional support during and after chemotherapy and provide evidence to inform long-term survivorship care strategies.